Adición de extracto de orégano (origanum vulgare) en la alimentación de cerdos en fase de engorde y su efecto en parámetros productivos - Andrade Castro, Galo Vinicio (2022)
The purpose of this research was to evaluate the effect of improving Kydo® extract (Origanum vulgare) in fattening pigs, its effect on production parameters and fecal antibacterial activity (CFU/g) (Staphylococcus aureus and Escherichia coli). Eighteen piglets (males) of the Landrace x Pietrain breed were randomly selected from homogeneous litters of 100 days of age (fattening) distributed in three treatments: control (T0), treatment one (T1) 0.5% of oregano extract was added to the feed and in treatment two (T2) 1%, organized in a comparative design. The means were compared with the Tukey test (p<0.05) using the infostat statistical package, indicating that the results reflected a highly significant difference p<0.0001, in which the treatment (T0) obtained a weight gain of 17.3kg and a feed conversion of 4.83kg/kg, (T1) obtained a weight gain of 29.31kg and a feed conversion of 2.83kg/kg and, obtaining the best result in (T2) with a weight gain of 37.4kg and a feed conversion of 2.25kg/kg. The antibacterial activity showed significant differences in CFU/g for Staphylococcus aureus and Escherichia coli in the +T2, which is why, through the research carried out, it is concluded that the proposed hypothesis has been accepted, since oregano oil supplementation improved the productive parameters in fattening pigs, generating an alternative as a growth promoter to replace antibiotics.